Impacts of various amendments on the microbial communities and soil organic carbon of coastal saline–alkali soil in the Yellow River Delta - Liu, Runang; Liang, Beijia; Zhao, Huili; Zhao, Ying (Frontiers in Microbiology, 2023)
The utilization of industrial and agricultural resources, such as desulfurization gypsum and straw, to improve saline alkali land is increasingly favored. However, there is still a lack of comprehensive study on the mechanism of organic carbon turnover under the conditions of desulfurization gypsum and straw application. We studied the changes in soil chemical performance, microbial diversity, and microbial community structure in soils with various levels of straw addition (no straw, S0; low straw, Sl; medium straw, Sm; high straw, Sh) and the addition of different levels of gypsum (no gypsum, DG0; low gypsum, DGl; high gypsum, DGh) in a 120-day incubation experiment. The bacterial and fungal community richness was higher in the SmDGl treatment than in the SmDG0 treatment. The microbial community evenness showed a similar pattern between the SmDGl and SmDG0 treatments. The combination of the straw and desulfurization gypsum treatments altered the relative abundance of the main bacterial phyla Bacteroidetes, Firmicutes, and the dominant fungal class Sordariomycetes, which increased with the enhancement of SOC ratio. The combination of the straw and desulfurization gypsum treatments, particularly SmDGl, significantly decreased the soil pH and exchangeable sodium percentage (ESP), while it increased the soil organic carbon, microbial biomass carbon, and activities of soil enzymes. Improvement in the soil salinization environment clearly drove the changes in bacterial α-diversity and community, particularly those in the soil carbon fractions and ESP. In conclusion, these findings provide a strong framework to determine the impact of application practices on soil restoration, and the information gained in this study will help to develop more sustainable and effective integrated strategies for the restoration of saline-alkali soil.